2017
DOI: 10.18203/2320-1770.ijrcog20171966
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about reproductive health, contraceptive methods, STDs including HIV/AIDS, and HPV vaccine, among adolescent girls in district Faridkot in Punjab

Abstract: Background: Adolescents are more vulnerable than adults to unplanned pregnancies and sexually transmitted diseases including HIV/AIDS. Female adolescents have a higher risk of contracting an STD than their male counterparts. Hence creating awareness in them about reproductive health is the need of the hour.Methods: This was a cross sectional school based Study which was conducted in various schools of Faridkot city of Punjab where 400 Adolescent girls of class 11th and 12th age between 16-19 years, studying in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Regarding the awareness about the safest method to prevent STIs, only 38.4% of study subjects in the present study answered condoms as the safest method. A cross-sectional study conducted in various schools of Faridkot city of Punjab by Grover et al [20] showed that about 62.25% of the girls knew about condoms for safe sex. Another study conducted by Renjhen et al [21] showed that around 85% of subjects knew about condoms but only 40% had knowledge about contraceptive pills.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the awareness about the safest method to prevent STIs, only 38.4% of study subjects in the present study answered condoms as the safest method. A cross-sectional study conducted in various schools of Faridkot city of Punjab by Grover et al [20] showed that about 62.25% of the girls knew about condoms for safe sex. Another study conducted by Renjhen et al [21] showed that around 85% of subjects knew about condoms but only 40% had knowledge about contraceptive pills.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted across different parts of India revealed that, the awareness level for reproductive health among the adolescents is below average. [17][18][19][20][21][22] However, studies conducted among science students or medical students reported a considerably high level of awareness for reproductive health. 23,24 Our study population also included only students pursuing health professional courses hence, a very high level of awareness was observed in our study, since study of reproductive health is an essential part of their curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these efforts and endeavors, challenges toward sound management of C. trachomatis and other STIs remain. One of the main hurdles is the lack of awareness on SRH-related topic within Indian communities, particularly among youths ( 39 ). Cultural and traditional factors also impact negatively on STI control.…”
Section: Current Initiatives and Barriers To Chlamydia Tracmentioning
confidence: 99%